CONSTRUCTING CULINARY AUTHENTICITY THROUGH A CORPUS ASSISTED DISCOURSE ANALYSIS OF BATAK TOBA CUISINE ON INSTAGRAM - Devi Melisa Saragi; Febrimarini Sinulingga (Prodi Sastra Inggris UKI, 2026)
This study tries to examine how culinary authenticity of Batak Toba cuisine is represented in English language Instagram captions from a corpus assisted discourse perspective. By applying the multidimensional authenticity frameworks proposed by Johnston and Baumann (2010) and Freedman and Jurafsky (2011), alongside collocation and concordance analysis informed by Hunston (2002) and Baker (2006), the research aims to identify and analyse how lexical patterns construct various dimensions of authenticity such as sensory, procedural, historical, and locality aspects. This descriptive qualitative research employs a corpus assisted method, using Sketch Engine to collect and analyse 53 captions drawn from two Batak Toba culinary Instagram accounts. The findings reveal that the prominent collocational patterns produce six authenticity dimensions namely sensory, procedural, material, historical, locality, and social functioning to frame Batak cuisine as culturally rooted, traditionally sustained, and socially meaningful. Through Fairclough’s Critical Discourse Analysis, the study further shows that these lexical constructions undergo recontextualization which transforms everyday culinary elements into symbolic markers of heritage and identity. Ultimately, the results demonstrate how digital food discourse linguistically shapes and perpetuates Batak Toba cultural values in contemporary online spaces.